Impact of Ankylosing Spondylitis on Sexual and Vocational Life - Fatma Peker; M. Ali Taşkaynatan; Ahmet Özgül; T. Alp Kalyon (Archives of Rheumatology, 2006)
Objective: Although work place difficulties and sexual problems are not uncommon in ankylosing spondilitis (AS), there has been insufficient emphasis on them. The aim of this study was to reveal the effects of AS in work life and sexual functions. Patients and Methods: 94 young male AS patients fulfilling modified New York criteria, with the mean age of 24.33 years and mean disease duration of 2.53±0.96 years, were included in the study. Standard questionnaires addressing sexual and vocational lives were applied to all patients. Results were assessed with Likert type scale. Sexual desire, intercourse frequency and finding pleasure in intercourse were questioned for the assessment of sexual life. Status of being on work or out of work, unemployment or retirement reason and work satisfaction were questioned for the assessment of vocational life. Results were compared with the results of specific questionnaires for the assessment of AS, BASFI, BASDAI, BAS-G and BASMI which assess the disease activity and outcome. Results: There were statistically significant correlations between sexual life parameters and indices of BASFI and BASDAI. Correlations between vocational life parameters and AS indices of BASFI, BASDAI, BAS-G and BASMI were found statistically significant. Conclusion: As a result, we concluded that vocational and sexual life of the patients with AS are being influenced negatively by the disease’s impact on functional status and activities of daily living. (Rheumatism 2006; 21: 100-4)